THORACIC SURGERYIntratumoral lymphatic vessel density, and intratumoral and peritumoral lymphatic vessel invasion as predictive factors of lymph node metastasis and prognostic factors in esophageal cancer - Kozłowski, Mirosław; Niklińska, Wiesława; Naumnik, Wojciech; Laudański, Wojciech; Milewski, Robert; Nikliński, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
In esophageal cancer, metastases in regional lymph nodes occur early and are a poor prognostic factor. We studied intratumoral and peritumoral lymphatic vessel density, and intratumoral and peritumoral lymphatic vessel invasion using D2-40 immunohistochemical staining in 74 resected esophageal cancer specimens and correlated results with patients’ clinicopathologic features and outcomes. Results were analyzed by univariate and multivariate logistic regression as well as univariate and multivariate survival analysis. The peritumoral lymphatic vessel density was significantly higher than the intratumoral lymphatic vessel density (p < 0.001). The peritumoral lymphatic vessel density and intratumoral lymphatic vessel density positively correlated with lymph node metastasis, tumor stage, depth of tumor invasion, and residual tumor. Positive intratumoral lymphatic vessel invasion and peritumoral lymphatic vessel invasion were significantly correlated with lymph node metastasis, tumor size, tumor depth, stage, and residual tumor. Multivariate logistic regression analysis identified intratumoral lymphatic vessel density (p = 0.028) and peritumoral lymphatic vessel invasion (p = 0.036) as risk factors of lymph node metastasis. Cox regression analysis showed that intratumoral lymphatic vessel invasion and peritumoral lymphatic vessel invasion are independent prognostic factors of disease-free survival (p = 0.018, p = 0.021), cancer-specific survival (p = 0.016, p = 0.025), and overall survival (p = 0.017, p = 0.02). Intratumoral lymphatics and peritumoral lymphatic vessel invasion are predictive factors of lymph node metastasis. Intratumoral and peritumoral lymphatic vessel invasion are independent prognostic factors in locally advanced esophageal cancer.